Маленькая Баба-Яга - Пройслер Отфрид (Книги - мои друзья, 2015)
Экземпляры: ф.18 (20160128) / Инвентарный номер: 537 / Цена: / Сис.шифр: 84(4Гем)-4 / Авт.знак: П 80 / ГРНТИ: 17.82.93 / ББК: 84(4Гем)-4